Algeria : Background Paper. (IMF Staff Country Reports; Country Report, 1995)
This paper provides information on some of the most salient aspects of Algeria's economy as well as statistical information for the IMF staff report on the 1995 Article IV Consultation and Request for an Extended Arrangement. The paper also reviews the reforms that have been made to the social safety net over recent years. It also describes the shift away from a system of generalized subsidies, which has been inefficient and costly, to a system of targeted subsidies coupled with the introduction of a public works program and an unemployment insurance scheme.